2015
DOI: 10.1186/s12958-015-0096-y
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Intracytoplasmic morphologically selected sperm injection versus conventional intracytoplasmic sperm injection: a randomized controlled trial

Abstract: BackgroundIntracytoplasmic morphologically selected sperm injection (IMSI) is still proposed and employed in the clinical practice to improve the reproductive outcome in infertile couples scheduled for conventional intracytoplasmic sperm injection (cICSI). The aim of the current randomized controlled trial (RCT) was to test the hypothesis that IMSI gives a better live birth delivery rate than cICSI.MethodsInfertile couples scheduled for their first cICSI cycle for male factor were allocated using a simple rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
11

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 38 publications
(65 reference statements)
2
10
0
11
Order By: Relevance
“…Although there were trends for higher implantation, clinical pregnancies, and live birth rates in the IMSI group, using the technique did not reveal an improvement in the clinical outcome compared with ICSI [57,58]. The authors of the current publication, therefore, will try to discuss the benefits of IMSI in cases of patients with repeated implantation failures, severe male factor infertility, and advanced paternal and maternal age.…”
Section: Imsi Should Not Be Used For Allmentioning
confidence: 94%
“…Although there were trends for higher implantation, clinical pregnancies, and live birth rates in the IMSI group, using the technique did not reveal an improvement in the clinical outcome compared with ICSI [57,58]. The authors of the current publication, therefore, will try to discuss the benefits of IMSI in cases of patients with repeated implantation failures, severe male factor infertility, and advanced paternal and maternal age.…”
Section: Imsi Should Not Be Used For Allmentioning
confidence: 94%
“…Giovanni et al . reported that IMSI did not improve fertilization, cleavage, pregnancy and live birth in unselected couples with male factor infertility (La Sala et al ., ). Orief et al .…”
Section: High Magnification Imaging Systemmentioning
confidence: 97%
“…Although, significantly higher normal fertilization rate was achieved in the IMSI group, but cleavage rate, top quality embryos, implantation and pregnancy were not improved with IMSI (Gong et al, 2015). Giovanni et al reported that IMSI did not improve fertilization, cleavage, pregnancy and live birth in unselected couples with male factor infertility (La Sala et al, 2015). Orief et al concluded in patients with severe male factor infertility and repeated ICSI failure, IMSI did not provide better results in fertilization, cleavage, pregnancy and implantation rates (Orief et al, 2016).…”
Section: Msome/imsi and Art Outcomementioning
confidence: 99%
“…Only two further randomized trials have been published since this review and neither reported an increase in live birth. (54,55). A systematic review of both randomized and non-randomized studies suggested benefit in the non-randomized studies but not in the randomized studies (56).…”
Section: Intracytoplasmic Morphologically Selected Sperm Injectionmentioning
confidence: 99%